Comparison of Time Utilization of Urban, Rural and Tribal Farmwomen in Farming and Post-Harvest Activities - Bellurkar, Chitra M. (IJRDO - Journal of Applied Management Science, 2017)
Farm women constitute so significant part of working women population in ourcountry that it necessitates a fuller understanding of their status and role not only as theynow are but as they may be in future. The study was carried out from two agro–climaticzones of Maharashtra. Nanded district was selected from Central Maharashtra Plateauzone and Nagpur district was selected from Central Vidarbha zone. This research consistsample of 409 farmwomen for farming activities and 410 farmwomen for post-harvestactivities from urban, rural and tribal areas. In the present study, time spending pattern ofthe respondents was compared in farming and post-harvest activities for rabi and kharifseasons. Time spending of the respondents in both the seasons was recorded in days peryear. Overall it can be concluded that tribal respondents under this study utilized moretime i.e. 126.67 days per year for performing the farming activities followed by ruralwomen who spent 123.05 days. Urban women spent comparatively less time i.e. 104.06days for farming activities. For the post-harvest activities, urban women spent 77.93 daysper year whereas tribal women spent 47.82 days followed by rural women who spent46.37 days for both the seasons per year.